2021
DOI: 10.14198/obets2021.16.1.05
|View full text |Cite
|
Sign up to set email alerts
|

Sexismo y mitos del amor romántico en adolescentes que residen en centros de acogida

Abstract: La investigación explora la relación entre sexismo y la distorsión en mitos del amor romántico en adolescentes que residen en Centros de Acogida de Menores en Valencia (España). El diseño de investigación fue descriptivo transversal con una muestra de 147 adolescentes. Los resultados reflejan una relación estadísticamente significativa que indica que, a mayor sexismo en los y las adolescentes, mayores son las distorsiones románticas. Se identificaron mayores niveles de sexismo hacia las mujeres y mitos del amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 44 publications
1
8
0
2
Order By: Relevance
“…The present research took a rigorous psychometric approach to the Myths, Fallacies and Erroneous Beliefs about the Ideal to assess romantic beliefs in relation to our current ing of the love construct. This scale had been previously used in research (Bisquert-Bover et al, 2019;Carbonell & Mestre, 2018;Picado et al, 2019) and practice (Pedrero & Leiva, 2014;Ruiz-Palomino et al, 2015), but no previous evidence of its validity and reliability had been reported. Hence, this study aimed at providing evidence of the scale's rigor and quality for either interpretation of previously published results and future use of the scale.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The present research took a rigorous psychometric approach to the Myths, Fallacies and Erroneous Beliefs about the Ideal to assess romantic beliefs in relation to our current ing of the love construct. This scale had been previously used in research (Bisquert-Bover et al, 2019;Carbonell & Mestre, 2018;Picado et al, 2019) and practice (Pedrero & Leiva, 2014;Ruiz-Palomino et al, 2015), but no previous evidence of its validity and reliability had been reported. Hence, this study aimed at providing evidence of the scale's rigor and quality for either interpretation of previously published results and future use of the scale.…”
Section: Discussionmentioning
confidence: 99%
“…Based upon previous work by De la Peña et al (2011), who developed item content and the initial theoretical structure of the Myths, Fallacies and Erroneous Beliefs about the Ideal of Romantic Love Scale, this paper presents a psychometric study of a pre-existing scale which had been previously employed both in Spanish (Bisquert-Bover et al, 2019;Carbonell & Mestre, 2018;Pedrero & Leiva, 2014;Picado et al, 2019;Ruiz-Palomino et al, 2015) and Mexican (Galicia et al, 2019) samples. The factorial structure of the scale was best represented by the one-factor solution, in which all 18 items except for item 4, which showed a low and statistically non-significant (p > .05) factor loading, were collapsed onto a single factor of romantic beliefs, in contrast to the original authors' proposed four-factor structure.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Meanwhile, benevolent sexism, a more hidden way of assuming the patriarchal beliefs, seems to lead to a significant increase of gender violence among adolescents [ 80 ] in non-traditional cultures as well as in the traditional ones. The belief that equality for women has already been achieved and that, therefore, no further political measures are needed for this purpose, and would increase the difficulties to really achieve equality [ 81 , 82 ], causes violence directed towards women to continue to perpetuate itself in society.…”
Section: Discussionmentioning
confidence: 99%